1992
DOI: 10.1128/jvi.66.8.4874-4883.1992
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of recombinant human immunodeficiency virus type 1 capsid protein in vitro

Abstract: The capsid protein (CA) (p24) of human immunodeficiency virus (HIV) type 1 expressed in Escherichia coli and purified to >90%o homogeneity was used to examine assembly in vitro and to probe the nature of interactions involved in the formation of capsid structures. The protein was detected in dimeric and oligomeric forms as indicated by molecular size measurements by gel filtration column chromatography, sedimentation through sucrose, and nondenaturing gel electrophoresis. Chemical cross-linking of CA molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(132 citation statements)
references
References 52 publications
12
120
0
Order By: Relevance
“…This manifests itself as a relatively weak complex that is consistent with the observations of monomeric SIV and HIV MAs in solution (Massiah et al, 1994;Matthews et al, 1994Matthews et al, , 1995. The additional driving force necessary for complete virion assembly is provided by oligomerization of the capsid protein (Ehrlich et al, 1992;Dorfman et al, 1994).…”
Section: Implications For Assemblysupporting
confidence: 83%
“…This manifests itself as a relatively weak complex that is consistent with the observations of monomeric SIV and HIV MAs in solution (Massiah et al, 1994;Matthews et al, 1994Matthews et al, , 1995. The additional driving force necessary for complete virion assembly is provided by oligomerization of the capsid protein (Ehrlich et al, 1992;Dorfman et al, 1994).…”
Section: Implications For Assemblysupporting
confidence: 83%
“…Accordingly, viral capsids of multiple copies of identical gene products are formed so as to minimize the genetic information required for virus assembly. In many cases, capsid protein dimers serve as building blocks for the assembly of plant and animal viruses (1,6,11,26,39,42,43). Under our experimental conditions, it was possible to resolve at least four discrete N protein oligomers, including dimers, trimers, tetramers, and pentamers.…”
Section: Discussionmentioning
confidence: 95%
“…Identification of CA-CA interfaces in the mature HIV-1 capsid CA multimers with the same structural organization as authentic mature capsids have been obtained by selfassembly of CA in vitro, even in the absence of any other biomolecule, and subjected to structural, biochemical and mutational analyses [27][28][29][30][31][32][33][34][35][36][37]. CryoEM studies of mature HIV-1 capsid-like particles assembled in vitro revealed that these are composed of an array of CA hexamers.…”
Section: Identification Of Ca-ca Interfaces In the Immature Hiv-1 Capsidmentioning
confidence: 99%